2021
DOI: 10.3390/biomedicines9111706
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Characteristics and Survival Rates of Resectable Pancreatic Ductal Adenocarcinoma according to Tumor Location

Abstract: The impact of tumor location on patient survival in pancreatic ductal adenocarcinoma (PDAC) remains controversial. This study investigated the association between primary tumor location and survival rates for resectable PDAC. Additionally, we assessed if this association remains consistent across categories of the Tumor-Node-Metastasis staging system. We analyzed 2471 patients who underwent surgical resection between 2000 and 2018 at a single center. Subgroup analysis was performed according to the Tumor-Node-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Several previous studies reported that clinicopathological factors such as tumor size, LN metastasis, surgical resection margin status, tumor markers (CA 19-9), SUV max on FDG-PET, and systemic inflammatory markers (neutrophil-lymphocyte ratio, lymphocyte-monocyte ratio, and Glasgow prognostic score) were associated with the prognosis following pancreatectomy for potentially R-PDAC ( 20 - 24 ). However, depending on the anatomical location of the PDAC, the prognosis and survival may vary ( 9 , 25 ). Studies focusing on left-sided PDAC with resectable status are rare.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies reported that clinicopathological factors such as tumor size, LN metastasis, surgical resection margin status, tumor markers (CA 19-9), SUV max on FDG-PET, and systemic inflammatory markers (neutrophil-lymphocyte ratio, lymphocyte-monocyte ratio, and Glasgow prognostic score) were associated with the prognosis following pancreatectomy for potentially R-PDAC ( 20 - 24 ). However, depending on the anatomical location of the PDAC, the prognosis and survival may vary ( 9 , 25 ). Studies focusing on left-sided PDAC with resectable status are rare.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, head tumors may be associated with longer overall survival due to more specific symptoms and, therefore, earlier diagnosis, while tail tumors are often larger and more aggressive [ 21 , 22 ]. On the other hand, tail tumors are linked to a lower lymph node ratio (the number of positive lymph nodes to the number of examined lymph nodes) and higher disease-specific survival rates than head tumors of the same stage of cancer [ 18 , 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%